Various plate theory used in the analysis of FGMs-A review. (2023) - Dash, Abhigyan; Kishore Joshi, Kamal; Jha, Pushkar; Behera, Asit; Kumar Mohapatra, Sambit; Rahul,
Abstract: This article reviews different plate theories which are used in the structural analysis of various functionally graded structures like shells/plates. The different plate theories are compared by introducing displacement field variables. It was found that first-order shear deformation theory (FSDT) and higher-order shear deformation theory (HSDT) are the most widely applicable theories for the structural examination of moderately thin functionally graded materials (FGMs) compared to classical laminate plate theory (CLPT). Since most researchers implemented two-dimensional theories which save considerable computational time and cost compared to three-dimensional theories. Therefore, this study is more focused on 2D-based theories. The end result of this study can be highly useful for researchers and designers in selecting appropriate theories to examine the structural behaviour of different composite materials.